2014
DOI: 10.1099/ijs.0.068635-0
|View full text |Cite
|
Sign up to set email alerts
|

Methanosarcina horonobensis sp. nov., a methanogenic archaeon isolated from a deep subsurface Miocene formation

Abstract: Thermoflexus hugenholtzii gen. nov., sp. nov., a thermophilic, microaerophilic, filamentous bacterium representing a novel class in the Chloroflexi, Thermoflexia classis nov., and description of Thermoflexaceae fam. nov. and Thermoflexales ord. nov. The description of Thermoflexales ord. nov. erroneously gives the family Thermoflexaceae as the nomenclatural type. The nomenclatural type of the new order is the genus Thermoflexus. The etymology of Thermoflexia class. nov. erroneously gives Thermoflexus as the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Acetate is not utilized for the production of methane by M. boonei and M. lacus but stimulates the growth of these species (Br€ auer et al, 2011;Borrel et al, 2012;Cadillo-Quiroz et al, 2014). Unlike other species of Methanosarcina that can grow on H 2 (Balch et al, 1979), M. horobensis grows on acetate but not on H 2 or formate (Shimizu et al, 2011). In this regard, the highest relative abundance of M. horobensis-affiliated sequences was detected in formate-supplemented Carex root incubations in which acetate was readily available (Figs 1 and 4).…”
Section: Methanogenesismentioning
confidence: 99%
“…Acetate is not utilized for the production of methane by M. boonei and M. lacus but stimulates the growth of these species (Br€ auer et al, 2011;Borrel et al, 2012;Cadillo-Quiroz et al, 2014). Unlike other species of Methanosarcina that can grow on H 2 (Balch et al, 1979), M. horobensis grows on acetate but not on H 2 or formate (Shimizu et al, 2011). In this regard, the highest relative abundance of M. horobensis-affiliated sequences was detected in formate-supplemented Carex root incubations in which acetate was readily available (Figs 1 and 4).…”
Section: Methanogenesismentioning
confidence: 99%
“…In siliceous mudstone at this study site (i.e. the Underground Research Center at Horonobe, Japan), potential microbial methanogenesis has been suggested for a sample collected below 200 m depth (Kato et al ., ), and a methanogenic archaeon has been isolated from 300 m depth (Shimizu et al ., ). The expression of biogeochemical reactions by any given microbial population in a subsurface environment is regulated by the species of electron acceptors in the groundwater, which in turn is controlled by the supply of rainwater and snowmelt, and by hydrological interactions with the surrounding geological setting (Kato et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In this study, we sampled groundwater at a depth of 140 m in a sedimentary formation where no positive DO concentration was observed and where the Eh value fluctuated, to investigate whether the environment is a potential site of denitrification or methanogenesis. The formation is shallower than one in which methanogenesis was detected in an earlier study (Shimizu et al ., ). Stable isotope signatures of carbon were determined to enable assessment of whether any methane present was of biogenic origin.…”
Section: Introductionmentioning
confidence: 97%
“…In deep subsurface environments, the pressure would of course be higher than that in the shallow subsurface, reaching about 10,000 kPa at 1 km depth (Jones et al, 2011). On Earth, living methanogens have been isolated from deep subsurface habitats (Kotelnikova et al, 1998;Lever et al, 2013;Shimizu et al, 2011), where the pressure is understandably higher compared to Mars. In addition, the activity of the marine methanogen Methanococcus jannaschii has been proved at a pressure of up to 75,000 kPa (Miller et al, 1988).…”
Section: Temperature [1c]mentioning
confidence: 98%